2017
DOI: 10.1111/eip.12528
|View full text |Cite
|
Sign up to set email alerts
|

Gender differences in first self‐perceived signs and symptoms in patients with an at‐risk mental state and first‐episode psychosis

Abstract: Our results suggest that only few and relatively small gender differences exist in the first self-perceived signs and symptoms. While men initially mainly notice negative/cognitive symptoms, women first notice (sub-threshold) positive and affective symptoms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
17
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(19 citation statements)
references
References 42 publications
2
17
0
Order By: Relevance
“…The gender differences observed in our study have also been noted by other researchers: among adolescents, females show greater frequencies and distress due to the symptoms (Fonseca‐Pedrero, Inchausti, Perez‐Albeniz, & Ortuno‐Sierra, 2018) especially positive and affective symptoms, as well as increased anxiety (Heitz et al, 2019). Other evidence suggests that men may suffer greater intensity of negative psychotic symptoms and increased aggression during the prodromal phase in comparison to females (Barajas, Ochoa, Obiols, & Lalucat‐Jo, 2015; Heitz et al, 2019). On the other hand, Karcher et al (2018) observed nonsignificant differences in distress scores in a group of younger kids, while the difference in total score was significant with a higher mean among boys.…”
Section: Discussionsupporting
confidence: 88%
“…The gender differences observed in our study have also been noted by other researchers: among adolescents, females show greater frequencies and distress due to the symptoms (Fonseca‐Pedrero, Inchausti, Perez‐Albeniz, & Ortuno‐Sierra, 2018) especially positive and affective symptoms, as well as increased anxiety (Heitz et al, 2019). Other evidence suggests that men may suffer greater intensity of negative psychotic symptoms and increased aggression during the prodromal phase in comparison to females (Barajas, Ochoa, Obiols, & Lalucat‐Jo, 2015; Heitz et al, 2019). On the other hand, Karcher et al (2018) observed nonsignificant differences in distress scores in a group of younger kids, while the difference in total score was significant with a higher mean among boys.…”
Section: Discussionsupporting
confidence: 88%
“…Findings relevant to the psychopathological positive dimension are inconsistent. A higher frequency of positive symptoms was reported in females than in males in several papers ( 5 , 42 , 67 , 69 , 73 , 74 ), including a study carried out in a large sample of patients with first-episode schizophrenia ( 69 ), while others reported an opposite pattern of differences ( 2 ). Interestingly, in a study exploring gender differences across diverse regions of the world ( 64 ), a greater severity of positive symptoms in females was found only in some regions, suggesting that psychosocial and cultural factors can impact the severity of this psychopathological dimension with a differential effect on gender.…”
Section: Psychopathological Featuresmentioning
confidence: 96%
“…In addition, we replicated the analysis based on gender cohorts separately, since studies have found differences between genders. For example, researchers in [22] indicate that while males initially show negative/cognitive symptoms, females present (sub-threshold) positive and affective symptoms. This also agrees with [23], where the authors state that males at high risk of psychosis displayed more pronounced negative symptoms, higher rates of past substance abuse disorders and higher deficits in social functioning than females.…”
Section: Experimental Designmentioning
confidence: 99%